Do stress, life satisfaction, depression and alcohol use predict quitting among Aboriginal and Torres Strait Islander smokers? - David P. Thomas; Maureen Davey; Anke E. van derSterren; Kathryn S. Panaretto; Louise Lyons (Elsevier, 2020)
Abstract Objective: To examine whether baseline measures of stress, life satisfaction, depression and alcohol use predict making or sustaining quit attempts in a national cohort of Aboriginal and Torres Strait Islander smokers. Methods: We analysed data from the nationally representative quota sample of 1,549 Aboriginal and Torres Strait Islander adults who reported smoking at least weekly in the Talking About The Smokes baseline survey (April 2012-October 2013) and the 759 who completed a follow‐up survey a year later (August 2013-August 2014). Results: More smokers who reported negative life satisfaction, feeling depressed, higher stress or drinking heavily less often than once a week at baseline made a quit attempt between the baseline and follow‐up surveys. In contrast, of these smokers who had made quit attempts between surveys, more who reported higher stress were able to sustain abstinence for at least one month; other associations were inconclusive. Conclusions and implications for public health: Health staff and Aboriginal and Torres Strait Islander smokers need not see being more stressed as an obstacle to quitting among Aboriginal and Torres Strait Islander people. Health staff should emphasise the benefits to mental health that come with successfully quitting smoking.